Human metapneumovirus - Arghyadeep Dutta,; Abhibroto Karmakar,; Baburajan Radha,; Ruby Dhar,; Arun Kumar,; Subhradip Karmakar, (Asian Journal of Medical Sciences, 2025)
Human metapneumovirus (HMPV) is a pre-existing negative sense RNA virus of the family Paramyxoviridae, manifesting lower respiratory tract infections in children and adults above the age of 65 years. It replicates in a gradient manner similar to other paramyxovirus and spreads through droplets (released during cough or sneeze) or direct contact with contaminated surfaces. This virus and its history of infections show a characteristic curve with time increasing periodically during the winter, like other respiratory infections such as influenza.